2019
DOI: 10.21037/atm.2019.11.19
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of statin therapy in pulmonary hypertension: a systematic review and meta-analysis

Abstract: Background: Pulmonary hypertension (PH) is a multi-causal disease and no satisfactory therapeutic strategies for it. Statins have been suggested as potential drugs in PH, whose effects in different clinic types of PH have not been conclusive. In this study, we included randomized controlled clinical trials (RCTs) evaluating the efficacy and safety of statins therapy in PH.Methods: We searched databases including Medline, Embase, Cochrane, PubMed and Web of science, with time up to January 1, 2019. With 95% con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Until now, the effectiveness of lipid-lowering therapy for pulmonary arterial hypertension (PAH) in previous studies has been controversial despite the association between metabolic disorder and PH [ 35 37 ]. In fact, it is confirmed that an intervention for dyslipidemia is less effective than the use of pulmonary vasodilators.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, the effectiveness of lipid-lowering therapy for pulmonary arterial hypertension (PAH) in previous studies has been controversial despite the association between metabolic disorder and PH [ 35 37 ]. In fact, it is confirmed that an intervention for dyslipidemia is less effective than the use of pulmonary vasodilators.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, the effectiveness of lipid lowering therapy for PAH in previous studies have been controversial, despite the association between metabolic disorder and PAH [32][33][34]. In fact, it is con rmed that an intervention for dyslipidemia is less effective than the use of pulmonary vasodilators.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of benefits might appear counterintuitive because statins have pleiotropic effects, such as lipid-lowering, antiproliferative, antioxidant, anti-inflammatory, and endothelial cell function–maintaining properties ( 49 ), which may be helpful in attenuating the progression of PAH. More recently, in 2019, another meta-analysis focused on clinical subgroup analysis: PAH and PH due to COPD ( 50 ). It suggests that statins can efficiently and safely reduce pulmonary arterial pressure in PH, especially in PH associated with COPD ( 50 ).…”
Section: Ldlr Regulates Oxidized Ldl Levelmentioning
confidence: 99%
“…More recently, in 2019, another meta-analysis focused on clinical subgroup analysis: PAH and PH due to COPD ( 50 ). It suggests that statins can efficiently and safely reduce pulmonary arterial pressure in PH, especially in PH associated with COPD ( 50 ). Therefore, the effect of lipid-lowering therapies remains controversial, but it appears that their effect varies between PH subtypes and further randomized controlled trials are needed to focus on the efficacy and safety of statin therapy in different subtypes.…”
Section: Ldlr Regulates Oxidized Ldl Levelmentioning
confidence: 99%
See 1 more Smart Citation